Long-term effects of best management practices on crop yield and nitrogen surplus - Laura Zavattaro; Chiara Costamagna; Carlo Grignani; Luca Bechini; Adelheid Spiegel; Taru Lehtinen; Gema Guzmán; Janine Krüger; Tommy D'Hose; Alicja Pecio; Frits K. van Evert; Hein F.M. ten Berge (Italian Journal of Agronomy)
Inherent in the concept of good agricultural practice (BMP) is that it improves resource use efficiency, mitigates environmental impact or increases farm profitability. However, it is usually impossible to achieve all the objectives, and trade-offs need to be accepted, such as a reduction in productivity together with a reduction in costs or an increase of soil organic matter. A European FP7 project, Catch-C (http://www.catch-c.eu) analyses the effects that different management practices have on productivity, mitigation of climate change and chemical, physical and biological soil fertility, based on simple indicators. Such indicators were collected from international literature, national scientific or technical journals, or grey literature that dealt with long-term field trials in Europe. We collected and analysed data from more than 350 experiments. This paper presents the overall results of the effects of a series of BMP have on crop productivity, soil nitrogen (N) uptake, N use efficiency end N balance. Important interactions with soil and climate types, crop and duration of the experiment were noticed for most BMPs. Rotations, also including double cropping, were among practices with more positive effects of productivity and N indicators. A slight reduction of yield counteracted benefits to soil quality and to climate change mitigation of minimum and no tillage, and of organic fertilisers.